Oral paracoccidioidomycosis: a study of 36 South American patients - Sposto, M. R.; Scully, C.; Dealmeida, O. P.; Jorge, J.; Graner, E.; Bozzo, L. (Mosby-year Book Inc, 1993)
Paracoccidioidomycosis (South American blastomycosis) is an uncommon, progressive systemic mycosis, virtually only seen in persons who have visited Latin America. Reports of oral lesions are extremely rare in the English-language literature. Thirty-six adults with oral lesions as the first sign of paracoccidioidomycosis are described; this appears to be the largest series in the dental literature. All had chronic proliferative mulberry-like ulcerated oral lesions; the diagnosis was confirmed histologically. The gingiva or alveolar process was the typical site, but lesions were also seen particularly on the palate and lip. Most of the patients proved to have detectable pulmonary involvement. Patients with lesions in the oropharynx, tongue, or floor of mouth all had confirmed pulmonary lesions.